2010
DOI: 10.1371/journal.pone.0015576
|View full text |Cite
|
Sign up to set email alerts
|

Polymers for Improving the In Vivo Transduction Efficiency of AAV2 Vectors

Abstract: BackgroundAdeno-associated virus has attracted great attention as vehicle for body-wide gene delivery. However, for the successful treatment of a disease such as Duchenne muscular dystrophy infusion of very large amounts of vectors is required. This not only raises questions about the technical feasibility of the large scale production but also about the overall safety of the approach. One way to overcome these problems would be to find strategies able to increase the in vivo efficiency.MethodologyHere, we inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…When s.c. xenograft models of LoVo or MDA-MB-231 cancers were established, BM-MSCs or iPSC-MSCs transduced with CMV-copGFP lentiviruses were injected via tail vein, and tumors were harvested 16 h later for section and qPCR assay of CMV promoter (50). For tumor initiating and growth assay, HCC1806 cancer cells were coinjected with BM-MSCs or iPSC-MSCs into the fourth mammary fat pad of NOD/SCID mice, and tumors were harvested 6 wk after inoculation.…”
mentioning
confidence: 99%
“…When s.c. xenograft models of LoVo or MDA-MB-231 cancers were established, BM-MSCs or iPSC-MSCs transduced with CMV-copGFP lentiviruses were injected via tail vein, and tumors were harvested 16 h later for section and qPCR assay of CMV promoter (50). For tumor initiating and growth assay, HCC1806 cancer cells were coinjected with BM-MSCs or iPSC-MSCs into the fourth mammary fat pad of NOD/SCID mice, and tumors were harvested 6 wk after inoculation.…”
mentioning
confidence: 99%
“…Cationic lipids and polymers have been shown to improve AAV2 transduction efficiency. 28,29 In one study, AAV-mediated insulin gene therapy was combined with preinjection of PEI in mice to achieve increased infection efficiency. 21 However, to our knowledge, we have used electrostatic surface coating of AAV2-VLPs for siRNA delivery for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…Coating of virus-like particles with polymers could have other benefits, such as protection of virus-like particles from neutralization by the immune system and improved infection efficiency. [28][29][30] It is important to know the mechanism of cell penetration and the mechanism of siRNA protection by the novel PEI-AAV2-VLPs. Investigation of these mechanisms in future studies will definitely provide more understanding of this new formulation.…”
Section: Discussionmentioning
confidence: 99%
“…Also, there are relatively few reports of polypeptides being used as scavenger receptor inhibitors. One study showed that pre-injection of polylysine improves the gene transfer efficiency of adeno-associated virus 10-fold when compared to the widely used anionic inhibitor poly-I [84]. Another study showed that pre-injection of scavenger receptor ligand peptides results in a modest 4-fold increase in helper dependent adenovirus activity upon pre-administration [39].…”
Section: Discussionmentioning
confidence: 99%
“…In viral gene delivery, the most frequently used adjuvant is the polyinosinic acid (poly I). Preadministration of poly I, has been used to extend the half-life of adenovirus, adeno-10 associated virus and measles virus by reducing KC uptake [38,[80][81][82][83][84]. One limitation to the widespread use of poly I is toxicity resulting in mortality [38].…”
Section: Scavenger Receptor Blockade (Figure 1-3a)mentioning
confidence: 99%